Host, Agent, and Environmental Risk Factors Associated with Dengue Hemorrhagic Fever Incidence and Control Measures in the Post-COVID-19 Era at Lambunga Public Health Center, East Flores District - Weraman, Pius; Dapaole, Jean; Muntasir, Muntasir; Sake Tira, Deviarbi; Sofia Lete Keraf, Anastasia (Journal of Neonatal Surgery, 2025)
The Weekly Outbreak Report (W2) of Dengue Hemorrhagic Fever (DHF) from the Flores Timur District Health Office indicates a markedly fluctuating increase in DHF cases over the past three years, with a notably high mortality rate in 2020 and 2021. The number of cases has continued to rise monthly, reaching a total of 11 by September 2021. The index case involved a fatality at the Lambunga Health Center, which prompted an Epidemiological Investigation (PE) conducted jointly by the District Health Office and the health center. The case resulted in one death, corresponding to a Case Fatality Rate (CFR) of 9.09%. This study aims to analyze the contributing factors associated with DHF incidence in the service area of the Lambunga Health Center, Flores Timur Regency. This study employed a mixed-methods approach, integrating both quantitative and qualitative research methodologies. The qualitative component utilized an observational analytical design, specifically a case-control study model. The findings indicate that occupational status, the presence of mosquito larvae, the use of mosquito nets, housing density, and substandard housing conditions collectively influenced 99% of DHF incidence in the Lambunga Health Center area. Among these, the most influential factor was the habit of using mosquito nets, which exhibited the highest odds ratio (OR) of 21.154